Edukasi Gema Cermat bagi Kelompok PKK di Desa Talok Kabupaten Tegal - Risma Firsty, Girly; Pramiastuti, Oktariani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Irrational use of drugs is still a significant health problem in Indonesia, one of the reasons being the lack of public understanding in self-medication. This community service activity aims to increase the knowledge and awareness of PKK members of Talok Village, Tegal Regency regarding the proper and rational use of drugs through the Gema Cermat Program education and introduction to herbal medicine science. The activity methods include providing educational materials, distributing poster media, pre-tests and post-tests, and Focus Group Discussions (FGD). A total of 50 participants took part in this activity, with the results showing an increase in the average knowledge score from 5.50 (pre-test) to 9.68 (post-test). These results indicate that the education provided is effective in increasing public understanding regarding the correct use of drugs. It is hoped that this activity can encourage more rational drug use behavior in the community. Keywords: Gema Cermat, rational drugs, community education, herbal medicine science